PSIX-17 Effects of dietary Allium mongolicum Regel leaves or probiotic complexes on mutton eating quality and antioxidant activities of DuHan sheep. - Ding, H (J Anim Sci, 2018)
Effects of dietary Allium mongolicum Regel leaves or probiotic complexes on mutton meat quality and antioxidant activities of DuHan sheep He Ding, Wangjing Liu, Changjin AO, Khas-Erdene College of Animal Science, Inner Mongolia Agricultural University, Hohhot 010018, China The aim of this study is to evaluate the effects of Allium mongolicum Regel leaves(AMRL) or probiotic complexes(PC) on mutton quality eating quality and antioxidant activities of DuHan sheep. A total of 12 DuHan sheep were randomly selected and equally divided into three groups as follows, Control group, only basal diets; AMRL group,basal diets plus AMRL(0.46%, dry matter basis); PC group,basal diets plus PC(4.35%, dry matter basis), amounts of the additives. After 75 days of feeding and before slaughter trial, blood samples were taken. After slaughter, samples the gluteus medius (GM) and biceps femoris (BF) muscles were taken for the assessment of meat eating quality. The results showed that dietary AMRL increased roupcolor L* value in both GM and BF muscles in the color B* value in the BF muscle compare to Control and PC group (P < 0.05), however dietary AMRL or PC had no effects on other mutton eating quality parameters (P > 0.05). The serum activity of T-AOC of AMRL group was higher (P < 0.05) than control and PC groups. Compared to the control group, SOD, CAT, GSH-Px activity in the AMRL group and PC group were higher (P < 0.05), while MDA was not different between groups (P > 0.05). Overall, the AMRL and PC maybe added to the diet to improve some meet color characteristics and serum antioxidant activites. [Image: see text]